RANCANG BANGUN SISTEM INFORMASI DESA BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) PADA DESA SUKATANI, KECAMATAN CIKANDE, KABUPATEN SERANG - BANTEN - Puspa Arundini, (2021)
Law Number 6 of 2014 concerning Villages has encouraged villages to play a role in building village social resilience, provide basic services, tackling poverty, improve the quality of human resources, and improve people's welfare. To realize the role of this village, it is necessary to have information technology support in conveying various information needed by the community and other stakeholders. This research was conducted with the aim of designing and building a web-based village information system using the Rapid Application Development (RAD) method. The results of this study are in the form of a web-based village information system with the application of information features displayed on the Sukatani Village website including Village Profiles, Village Government, Community Institutions, Population Data, Facilities & Infrastructure, and Village Activities which are expected to help realize the role of the village, especially the Village. Sukatani, Cikande District, Serang Regency - Banten.